Spectrometric analysis of the compatibility of succinic acid with iodinol and metronidazole in the animal wound-healing liposomal gel - V. V. Mosyagin; A. G. Belyaev (Аграрная наука Евро-Северо-Востока)
The expediency of including succinic acid (succinate) in wound healing gels has been studied and scientifically substantiated by infrared spectrometry. For this purpose, the interaction of antiseptic components of wound healing gels – metronidazole and iodinol with succinic acid in an aqueous medium was studied. In aqueous solutions of the studied substances, insignificant fluctuations of the wave numbers of the peak of 1642.27-1643.12 cm-1 were revealed, characterizing fluctuations in the C‒C valence bonds. Specific absorption peaks were also established: iodine compound with polyvinyl alcohol – 1555.22; 1232.06; 1066.00; metronidazole ‒ 2115.81, 1555.22, 1394.59, 1187.66 and 1088.40 and succinate – 2925.22, 2854.56, 2105.31, 1456.15, 1177.12, 1086.77. As the result of the conducted studies, it was found that succinic acid makes complex compounds with iodinol and metronidazole. The study of the IR spectra of the obtained compounds allows to suggest that they are formed by interaction of carboxyl group of succinic acid with C‒O groups of polyvinyl alcohol in iodinol and R2C=NH+ groups in metronidazole.